The joint associations of smoking and obesity with subsequent short and long sickness absence: a five year follow-up study with register-linkage - Eira Roos; Tea Lallukka; Eero Lahelma; Ossi Rahkonen (BMC, 2017)
Abstract Background Both smoking and obesity are separately associated with sickness absence. Unhealthy lifestyle habits and health conditions may occur concurrently yet studies focusing on their joint association are few. This study examined the joint associations of smoking and obesity with sickness absence (SA). Methods A mail survey among employees of the City of Helsinki, Finland, during 2000-2002 included data on obesity, smoking and covariates (N = 8960, response rate 67%, 80% women). These data were prospectively linked with register data on self- (1-3 days) and medically certified (4 days or longer) SA among those consenting to the linkage (n = 6986). Pregnant, underweight and those with missing data on key variables were excluded (n = 138). The total number of participants included in the analyses was 6847. The follow-up time was 5 years. Poisson regression was used to calculate rate ratios (RR). Results Among women and men smoking and obesity were associated with self-certified SA. Among women there was a joint association with self-certified SA (obese smokers RR 1.81, 95% CI 1.59-2.07). Among women and men smoking and obesity were jointly associated with medically certified SA (for obese smoking women RR 2.23, 95% CI 1.93-2.57, for obese smoking men RR 2.69, 95% CI 2.03-3.55). Associations remained after adjustments for socioeconomic position, working conditions, health behaviours and self-rated health. Conclusion Both smoking and obesity are jointly associated with all lengths of sickness absence. Support measures for smoking cessation and prevention of obesity could likely to reduce SA.